An Experimental Investigation into the Performance of a Nanofluid Based Concentrating Parabolic Solar Collector (NCPSC) - Sharma, Kapil (My University, 2014)
Solar collectors are widely used to harvest the solar energy and performance of these solar collectors depends upon various factors like collector & receiver material, solar intensity, nature of working fluid etc. It has been observed that nature & properties of the working fluid which flows through the collectors, greatly effects its performance. In the present study an attempt has been made to improve the performance of a parabolic solar collector by using nanofluids instead of conventional fluid like water as working fluid. The present investigation mainly focus on the nanofluid based concentrating parabolic solar collector (NCPSC). Nanofluids are the suspensions of metallic or non-metallic nanoparticles like aluminium, aluminium oxide, copper oxide etc. in base fluids like water, ethylene glycol, oil etc. The performance of a parabolic solar collector is investigated experimentally by studying the effect of alumina (Al2O3) & copper oxide (CuO) nanoparticles in water, as working fluids. Three mass flow rates (20, 40 & 60) l/hr and two particles volume concentrations 0.01% & 0.05% have been examined. The average size of nanoparticle is 20-30 nm. Nanofluids are prepared without using any surfactant. For water based copper oxide (CuO) & for water based alumina (Al2O3) nanofluid, for a concentration of 0.01% (vol.) the maximum instantaneous efficiency is found to be 13.57% and 10.1% whereas, thermal efficiency is 4.87% and 3.67% for a mass flow rate of 60 l/hr. Similarly for same mass flow rate & at volume concentration of 0.05% the maximum instantaneous efficiency is 18.4% and 10.37% & thermal efficiency found to be 6.6% and 3.74%. Comparison of water based alumina nanofluid is done with copper oxide nanofluid and it is observed that by using CuO nanofluid as a working fluid the value for maximum instantaneous & thermal efficiency is 8.16% & 5.14% for 60 l/hr & 20 l/hr mass flow rates with 0.01% concentration. Similarly, for 60 l/hr mass flow rate the observed value of maximum instantaneous & thermal efficiency is 8.75% & 3.06% with 0.05% volume concentration. Therefore, from the results it can be concluded that the performance of solar collector is remarkably enhanced by using nanofluids as working fluid in the solar collector.
ME, MED
Keywords: parabolic solar collector, efficiency, nanofluid, mass flow rate, concentration